2021
DOI: 10.1002/jhbp.1069
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of bloodstream infection on acute cholecystitis indicated for emergency cholecystectomy

Abstract: Background The significance of blood culture for acute cholecystitis remains unclear. Methods A retrospective cohort study was conducted on patients who underwent emergency cholecystectomy at Hyogo Prefectural Amagasaki General Medical Center to examine the clinical impact of bloodstream infection (BSI), focusing on the association of BSI with bactibilia and severity grade based on the Tokyo guidelines 2018 (TG18). Results Among 177 patients included in the study, 32 had positive and 145 had negative BSI. Sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
(91 reference statements)
0
1
0
Order By: Relevance
“…The second of the two additional benefits of utilizing the SAND balloon catheter in surgical procedures is the ability to confirm the results of bacterial bile culture. Although the significance of blood culture in AC remains controversial, Hanabata et al 18 concluded that liquid culture can identify bacteria that cannot be isolated by bile culture, and the authors thus emphasized the importance of blood culture. Our previous study 11 also indicated that AC after cardiovascular surgery is associated with severe cholecystitis and that blood culture examination is imperative in severe cholecystitis.…”
Section: Discussionmentioning
confidence: 99%
“…The second of the two additional benefits of utilizing the SAND balloon catheter in surgical procedures is the ability to confirm the results of bacterial bile culture. Although the significance of blood culture in AC remains controversial, Hanabata et al 18 concluded that liquid culture can identify bacteria that cannot be isolated by bile culture, and the authors thus emphasized the importance of blood culture. Our previous study 11 also indicated that AC after cardiovascular surgery is associated with severe cholecystitis and that blood culture examination is imperative in severe cholecystitis.…”
Section: Discussionmentioning
confidence: 99%